Primary small cell neuroendocrine carcinoma: a rare entity of bladder neoplasm - Ahmad Sabri, Nadiah; Baba, Farahlina; Wan Muhamad, Wan Muhamad Mokhzani; Bakrin, Ikmal Hisyam; Mat Zin, Anani Aila (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Primary small cell neuroendocrine carcinoma (SCNEC) is a rare high-grade malignant neoplasm with neuroen- docrine differentiation derived from the urothelium. Herein, we report a case which presented with symptomatic anaemia secondary to haematuria, complicated with acute kidney injury following obstructive uropathy caused by the SCNEC, along with the discussion of the clinical presentation, radiological imaging and pathological findings of the disease.